The regulation of contrast ratio of polymer-dispersed liquid crystals (PDLCs) via polyvinyl alcohol (PVA) nanofibers. Issue 1 (13th April 2022) - Yu, Ping; Zhao, Yuzhen; He, Zemin; Ma, Cheng; Gao, Jianjing; Zhao, Yang; Zhang, Haiquan; Miao, Zongcheng
Abstract: In this study, a method to regulate the visible transmittance in off-state ( T off ) and the contrast ratio (CR) for polymer-dispersed liquid crystals (PDLCs) via electrospinning polyvinyl alcohol (PVA) nanofibers on ITO surfaces in liquid crystal cells was reported. The PDLC samples were prepared in the conventional liquid crystal cells and in the nanofiber cells. The results indicated that the sample in the nanofiber cell presented a lower T off and a larger CR in comparison with the sample in the conventional cell if the samples were prepared under the same UV light.